Establishing the Attention-Distractibility Trait. (February 2016) - Forster, Sophie; Lavie, Nilli
Failures to focus attention will affect any task engagement (e.g., at work, in the classroom, when driving). At the clinical end, distractibility is a diagnostic criterion of attention-deficit/hyperactivity disorder (ADHD). In this study, we examined whether the inability to maintain attentional focus varies in the overall population in the form of an attention-distractibility trait. To test this idea, we administered an ADHD diagnostic tool to a sample of healthy participants and assessed the relationship between ADHD symptoms and task distraction. ADHD symptom summary scores were significantly positively associated with distractor interference in letter-search and name-classification tasks (as measured by reaction time), as long as the distractors were irrelevant (cartoon images) rather than relevant (i.e., compatible or incompatible with target names). Higher perceptual load during a task eliminated distraction irrespective of ADHD score. These findings suggest the existence of an attention-distractibility trait that confers vulnerability to irrelevant distraction, which can be remedied by increasing the level of perceptual load during the task.